The promiscuous development of an unconventional Qa1b-restricted T cell population - Manoharan Valerio, Michael; Arana, Kathya; Guan, Jian; Chan, Shiao Wei; Yang, Xiaokun; Kurd, Nadia; Lee, Angus; Shastri, Nilabh; Coscoy, Laurent; Robey, Ellen A. (Frontiers in Immunology, 2023)
MHC-E restricted CD8 T cells show promise in vaccine settings, but their development and specificity remain poorly understood. Here we focus on a CD8 T cell population reactive to a self-peptide (FL9) bound to mouse MHC-E (Qa-1 b ) that is presented in response to loss of the MHC I processing enzyme ERAAP, termed QFL T cells. We find that mature QFL thymocytes are predominantly CD8ab+CD4-, show signs of agonist selection, and give rise to both CD8aa and CD8ab intraepithelial lymphocytes (IEL), as well as memory phenotype CD8ab T cells. QFL T cells require the MHC I subunit b-2 microglobulin (b2m), but do not require Qa1 b or classical MHC I for positive selection. However, QFL thymocytes do require Qa1 b for agonist selection and full functionality. Our data highlight the relaxed requirements for positive selection of an MHC-E restricted T cell population and suggest a CD8ab+CD4-pathway for development of CD8aa IELs.